658 An Audit of Frequency of Cancer Genetics Referral in Patients with a Family History of Colorectal Cancer. (4th May 2021) - Abbakar, M; James, T; Boxall, P; Lim, M
Abstract: Introduction: Guidelines on the management of hereditary colorectal cancers were updated in 2019. In this study, data from patients within the colonoscopy surveillance programme for hereditary cancer at York Teaching Hospitals Trust were analysed to assess category of risk and appropriateness of referrals to regional geneticists. Method: After examination of electronic records and clinical notes, patients were assigned a risk category of average, moderate or high according to the Amsterdam criteria and latest BSG/ACPGBI/UKCGG guidelines. Patients were then assessed to see if a concurrent referral had been made to the regional cancer genetic services. Results: There were 228 patients. 72(31.6%) patients were in the average, 81(35.5%) in the moderate and 41(18%) were in the high-risk category. 34 (14.9%) patients with insufficient data and/or assessments were in the indeterminate category. 18 of 72 (25%) patients with average risk were unnecessarily referred to the regional genetics team, while 5/41(12%) of high-risk patients were not. A large proportion of patients with insufficient data (19/34, 55.8%) were rightly or wrongly, referred to the regional genetics team. Conclusions: Assessment of hereditary cancer risk is difficult in the absence of good quality information. Risk assessment may be improved with use of a dedicated family history questionnaire/template - this facilitates identification of high-risk patients that benefit most from referral to geneticists.